Growth Performance and Profitability Analysis of Five-Chicken Strains in South Western Nigeria - Atansuyi , A.J.; Ilori, O.D.; Chineke, C.A.; Adebayo, O.T. (International Journal of Poultry Science, 2022)
Objective: This experiment was conducted to investigate the growth performance, carcass and organ traits and profitability of five-chicken strains in South-western Nigeria. Materials and Methods: A total of 300 birds comprising five strains, 60 birds per strain, were used for the experiment. Each strain was made of ratio 30:30 males to females. The experiment spanned through eight weeks and the birds were distributed based on their strains and sexes into ten treatments of 30 birds with three replicates of 10 birds each. At the end of 8th week, 12 birds (6 males and6 females) were randomly selected for analyses. Results: Analytical results showed that genotype significantly influenced (p